Characterization of surface-states in a hollow core photonic crystal fiber - Lamilla, Erick; Faria, Maicon S.; Aldaya, Ivan [UNESP]; Jarschel, Paulo F.; Pita, Julián L.; Dainese, Paulo (Optica Publishing Group, 2018)
Surface or edge states represent an important class of modes in various photonic crystal systems such as in dielectric topological insulators and in photonic crystal fibers. In the later, strong attenuation peaks in the transmission spectrum are attributed to coupling between surface and core-guided modes. Here, we explore a modified implementation of the spatial and spectral interference method to experimentally characterize surface modes in photonic crystal fibers. Using an external reference and a non-uniform Fourier transform windowing, the obtained spectrogram allows clear observation of anti-crossing behavior at wavelengths in which surface and core modes are strongly coupled. We also detect surface modes with different spatial symmetries, and give insight into mode families couple to the fundamental or high-order core modes, as well as the existence of uncoupled surface modes.